Understanding and addressing the global impact: A systematic review and cross-sectional bibliometric analysis of Langya henipavirus and pre-existing severe henipaviruses - Jian-Di Li; Yu-Qing Liu; Rong-Quan He; Zhi-Guang Huang; Wan-Ying Huang; Hong Huang; Zhi-Hong Liu; Gang Chen (Journal of Infection and Public Health)
In 2022, Langya henipavirus was identified in patients with fever in eastern China. This study provides an overview of the scientific landscape, highlights research focus areas, and outlines potential future investigations. The relevant scientific literature was systematically searched and reviewed via advanced bibliometric techniques. Over the past two decades, henipavirus research has increased at an annual rate of 8.82 %. The United States leads in research output, with the Australian Animal Health Laboratory as the top institution. Most articles are published in the Journal of Virology, identified as the most influential journal along with researcher Wang LF. Current research focuses on “zoonosis,” “vaccine,” and “pathogenesis,” whereas future areas may include “molecular docking,” “immunoinformatics,” “climate change,” “antibodies,” “vaccines,” “glycoprotein,” and “ephrin-b2.” This study details henipavirus research, highlighting key players, trends, and future directions. These insights will guide future efforts to address the risks posed by novel Henipaviruses, such as Langya.